Fungi associated with Ips acuminatus (Coleoptera: Curculionidae) in Ukraine with a special emphasis on pathogenicity of ophiostomatoid species - Kateryna DAVYDENKO; Rimvydas VASAITIS; Audrius MENKIS (European Journal of Entomology, 2017)
Conifer bark beetles are well known to be associated with fungal complexes, which consist of pathogenic ophiostomatoid fungi as well as obligate saprotroph species. However, there is little information on fungi associated with Ips acuminatus in central and eastern Europe. The aim of the study was to investigate the composition of the fungal communities associated with the pine engraver beetle, I. acuminatus, in the forest-steppe zone in Ukraine and to evaluate the pathogenicity of six associated ophiostomatoid species by inoculating three-year-old Scots pine seedlings with these fungi. In total, 384 adult beetles were collected from under the bark of declining and dead Scots pine trees at two different sites. Fungal culturing from 192 beetles resulted in 447 cultures and direct sequencing of ITS rRNA from 192 beetles in 496 high-quality sequences. Identification of the above revealed that the overall fungal community was composed of 60 species. Among these, the most common were Entomocorticium sp. (24.5%), Diplodia pinea (24.0%), Ophiostoma ips (16.7%), Sydowia polyspora (15.1%), Graphilbum cf rectangulosporium (15.1%), Ophiostoma minus (13.8%) and Cladosporium pini-ponderosae (13.0%). Pathogenicity tests were done using six species of ophiostomatoid fungi, which were inoculated into Scots pine seedlings. All ophiostomatoid fungi tested successfully infected seedlings of Scots pine with varying degrees of virulence. Ophiostoma minus was the only fungus that caused dieback in inoculated seedlings. It is concluded that I. acuminatus vectors a species-rich fungal community including pathogens such as D. pinea and O. minus. The fungal community reported in the present study is different from that reported in other regions of Europe. Pathogenicity tests showed that O. minus was the most virulent causing dieback in seedlings of Scots pine, while other fungi tested appeared to be only slightly pathogenic or completely non-pathogenic.